Atopic allergy resulted from exposure to HDM allergens in Amara city: southern Iraq - Abdullah, Younus Jasim (University of Thi-Qar Journal of Science, 2019)
House dust mites (HDM) are small creatures that live indoor in warm, moist places. Several studies found that HDM are important sources of airborne allergens that cause different allergic symptoms all over the world. With this mind, 200 persons suffering from different allergic symptoms were randomly selected in the current study aged between 7-60 years old from both gender. They all subjected to skin prick test by using standard allergen solution for HDM allergens Dermatophagoides farinae (D.F) and Dermatophagoides pteronussinus (D.P). The results showed that most frequent allergic disease related to exposure to HDM was asthma and allergic bronchitis(33 % and 28% respectively). Female sex have the higher percentage of response(61%) than males(39%). Also, the urban society were more sensitive than rural. Furthermore, workers were more allergic than employees. In conclusion: we observed that sensitization to HDM allergens is associated with airways allergy such as asthma and allergic bronchitis especially in females and workers. In addition the allergic symptoms increase with urbanization.